2017
DOI: 10.21037/jgo.2017.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Potential actionable targets in appendiceal cancer detected by immunohistochemistry, fluorescent in situ hybridization, and mutational analysis

Abstract: Background: Appendiceal cancers are rare and consist of carcinoid, mucocele, pseudomyxoma peritonei (PMP), goblet cell carcinoma, lymphoma, and adenocarcinoma histologies. Current treatment involves surgical resection or debulking, but no standard exists for adjuvant chemotherapy or treatment for metastatic disease. Methods: Samples were identified from approximately 60,000 global tumors analyzed at a referral molecular profiling CLIA-certified laboratory. A total of 588 samples with appendix primary tumor sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 24 publications
7
54
3
2
Order By: Relevance
“…The results indicate that BRAF ‐mutated serrated polyps are non‐progressive lesions and are not likely to be the precursor of other tumour types. In contrast to our results, previous studies have reported much lower frequencies of BRAF mutations in the serrated lesions of the appendix . Yantiss et al identified BRAF mutations in 11 of 33 (33%) non‐dysplastic serrated lesions and five of 23 (22%) dysplastic serrated lesions .…”
Section: Discussioncontrasting
confidence: 99%
“…The results indicate that BRAF ‐mutated serrated polyps are non‐progressive lesions and are not likely to be the precursor of other tumour types. In contrast to our results, previous studies have reported much lower frequencies of BRAF mutations in the serrated lesions of the appendix . Yantiss et al identified BRAF mutations in 11 of 33 (33%) non‐dysplastic serrated lesions and five of 23 (22%) dysplastic serrated lesions .…”
Section: Discussioncontrasting
confidence: 99%
“…13,26,30,33,34 The diagnosis of ocular melanoma is particularly strongly associated (OR = 2.09, p < 0.0001) which is consistent with previous literature findings. 21,22,31 …”
Section: Resultssupporting
confidence: 91%
“…As we embark on these prospective studies, it is important to recognize just how little insight we possess about the intrinsic characteristics of the disease. We have yet to identify prognostic or predictive biomarkers, potential molecular drivers or immune signatures that could impact targeted-or immune-therapy selection and clinical trial eligibility for AGCC patients [12, 13]. Gaining more information about the disease through powerful tools such as next-generation sequencing remains an area of need.…”
Section: Resultsmentioning
confidence: 99%